Versatile synthesis of activated carbon from coconut shells: a method for cyanide adsorption in artisanal and small-scale gold mining wastewater - Achmad Gus Fahmi; Zainal Abidin; Cecep Kusmana; Erliza Noor (Journal of Degraded and Mining Lands Management, 2022)
Over the next years, Indonesia’s traditional gold mining technique (that employs mercury amalgamation) will be gradually replaced by cyanidation as a result of a Presidential Decree that has been recently issued. The cyanide-containing waste resulting from the processing tanks of this new method will be generally sedimented and flow directly into the surrounding small rivers. This study aimed to reduce the impact of cyanide contamination on the environment by using the simple activated carbon that can be produced by artisanal small-scale gold mining (ASGM). Water samples were taken from artificial wastewater as part of three replications. The highest recorded removal of cyanide from sewage was 98.43%, with an equilibrium reached at a fixed adsorbent dosage of 0.05 g over a contact time of 24 hours. Cyanide adsorption was also found to be pH-dependent, with the highest cyanide adsorption occurring at a pH of 8. The adsorption capacity for cyanide was estimated at 12.51 mg g-1 of the adsorbent, and it was considered to function based on a Langmuir isotherm model. The findings of this study confirm that the utilized glass wool in the assessed method can increase the yield of activated carbon, thereby offering a low-cost and effective adsorbent that can be used in order to remove cyanide from ASGM wastewater.